Morphological and Biochemical Characterization of a Cellulose-Degrading Bacteria isolated from Horse Feces (Equus caballus) - Ash Siddiq, R.H.; Cahyo, Budiman; Haslina, Asis; Rafida, Razali; Epi, Taufik (IOP Publishing Ltd, 2025)
Cellulase is a widely developed enzyme for industrial applications, produced by various sources, including bacteria. While numerous bacteria are known to produce cellulose-degrading enzymes (CDE), further exploration is needed to discover unique and highly active CDEs. This study focuses on screening, identifying, and characterizing cellulose-degrading bacteria (CDB) from horse faces, which are considered an excellent source for such bacteria. Fecal samples were collected from Megastar Horse Farm in Batu, Malang, and screened on carboxymethyl cellulose (CMC)-containing agar, incubated at 37 °C. The colonies that formed halo zones on the agar were isolated, and their genomic DNA was extracted for 16S rRNA gene amplification. Sequence analysis revealed that the isolate showed over 98% similarity to B. amyloliquefaciens SLBD and was subsequently labeled as B. amyloliquefaciens SLBD. Gram staining and scanning electron microscopy confirmed that B. amyloliquefaciens SLBD is Gram-positive with a rod-shaped morphology. B. amyloliquefaciens SLBD also grew optimally in Luria-Bertani (LB) medium at 37 °C. The CDE activity of this strain was assessed using its extracellular fraction against CMC and mannan oligosaccharides (MOS), revealing a substrate-dependent activity profile, with CMC being the preferred substrate.